Feasibility and Engagement of Multi-domain Cognitive Training in Community-Dwelling Healthy Elderly in Shanghai - Yu, Ze; Wu, Xia; Jiang, Rui; Chen, You; Shen, Yuan; Li, Chunbo; Feng, Wei (Frontiers in Psychiatry, 2022)
Abstract: Background: In recent years, cognitive training has been one of the important non-pharmaceutical treatment methods which could delay cognitive decline and improve quality of life in the elderly. In different types of cognitive training, both the cognitive domains focused on and their training methods widely vary. This study aimed to explore the feasibility and engagement of multi-domain cognitive training in Chinese community-dwelling healthy elderly. Methods: Based on the cluster sampling method, a total of 151 healthy elderly, aged 70 or above, who lived in the neighborhoods in Shanghai met the inclusion criteria and agreed to participate in the study. Among them, 90 participants were assigned to the cognitive training group (intervention group), 61 were assigned to the no cognitive training group (control group). Participants in the intervention group attended a one-hour multi-domain cognitive training course twice a week for 12 weeks (total of 24 times), which targeted memory, reasoning, strategy-based problem-solving skills, etc. The control group did not receive any intervention. Results: There was a significant increase in test scores of Story Recall (t=-8.61, p=0.00) and Raven’s Standard Progressive Matrices (RSPM) (t=-10.60, p=0.00) after in-class interventions. The overall completion of homework was 77.78%. 50% of the 90 participants completed self-training. The top three self-training methods were physical exercise, reading books and newspapers, and watching TV. The overall attendance rate of the intervention group was 76.14%, and over 50% of them had an attendance rate of 77.8%. The attendance rate was positively correlated with years of education and baseline SF-36 (Physical functioning, General health, Vitality, and Mental health) scores, while it was negatively correlated with baseline disease index and fatalism of personality indicators (p<0.05). Conclusion: The elderly with higher educational levels, better physical and psychological conditions had a higher engagement in multi-domain cognitive training. The training course proved to be rational, feasible, and effective for community-scale application. Keywords: healthy elderly, multi-domain cognitive training, feasibility, engagement, community